Extending the analysis of motor skills in relation to performance and laterality - Castaner, M.; Andueza, J.; Anguera, M. T.; Sanchez-Algarra, P. (Mixed methods research in the movement sciences: Case studies in sport, physical education and dance, 2014)
Case Study 1: How to observe spontaneous motor skills in natural contexts: from children's playgrounds to parkour Case Study 2: The laterality of motor skills: a complex merging of postural support and gestural precision. Although various disciplines have recognized the need to determine the possibilities of human movement, it is important to analyse in greater depth the most effective way of observing, evaluating and analysing the complexity of motor skills. The two case studies described in this chapter combine the use of observation instruments with statistic analysis and interviews or a discussion group. The first case study uses a specific observational system to analyse the motor skills employed during free movement in two natural contexts, namely children's playgrounds and public urban spaces. In the latter context the activity analysed is parkour, also known as free running, in which practitioners seek original and creative ways of moving through urban spaces. The qualitative and subsequently quantitative data derived from the observational analysis is here complemented by qualitative information gained through interviews with experts. In terms of mixed methods this corresponds to an explanatory sequential design. The second case study examines laterality- as a key aspect to be considered when analysing basic and specific motor skills. The specific focus is on two factors, postural support and gestural precision, which act in conjunction when performing any kind of motor skill. An instrument designed to record motor laterality is used to obtain an initial set of quantitative data, which are then complemented with qualitative data obtained through a discussion group involving experts in physical education. The purpose of this was to create a more dynamic version of the recording instrument, with wich new quantitative data could then be obtained. In terms of mixed methods this process corrosponds to an embedded design